Regional Anesthesia for Pacemaker Insertion. Issue 2 (March 1989) - Martin, Rene; Dupuis, Jean-Yves; Tetrault, Jean-Pierre
Abstract : Four local or regional anesthesia techniques for the insertion of cardiac pacemaker were studied prospectively in 40 patients. The four techniques studied were: local anesthesia, field block of the supraclavicular nerves, interscalene block at C4, and interscalene block at C6 . The three goals of the study were to find the technique that gave the best quality of analgesia, the incidence of complications related to each technique, and the area of sensory innervation of C4 . No technique was found to be superior to the others with regard to the quality of analgesia. Interscalene blocks at C4 and C6 were associated with complications and side effects more often than the two other techniques. The authors also suggest that the dermatome of C4 is not under the clavicle but above the clavicle. It was concluded that local anesthesia infiltration at the site of cardiac pacemaker insertion or field block of the supraclavicular nerves are the best techniques for cardiac pacemaker insertion.